Inovasi Pelayanan Pelanggan Berbasis Hasil Indeks Kepuasan Masyarakat (IKM) Di Perusahaan Umum Daerah Air Minum Tirta Moedal Kota Semarang - Farkhan Himie (Universitas 17 Agustus 1945, 2023)
Improving public services becomes an inevitability for government agencies as public service organizers. No exception for Tirta Moedal Drinking Water Perumda Semarang City, as a Regional Owned Enterprise (BUMD) is also inseparable from the demands of improving the quality of service to customers. Customer service innovation is a response to service problems that do not satisfy the community as customers. Customer dissatisfaction with customer complaints, information services and new connect services is very dominant for customer complaints. The Community Satisfaction Index (IKM) is one of the indicators of accountability for service performance in the public sector that cannot be ignored. The Community Satisfaction Index is an evaluation of the community as a customer for the performance of services provided to the community as customers that should be the basis for each service provider institution to make adjustments to customer expectations and service innovation. The rapid development of information technology also increases public awareness of its right to good service.